Lower urinary tract symptoms and benign prostatic hyperplasia : from research to bedside - Morgia, Giuseppe; Russo, Giorgio Ivan (ClinicalKey., 2018)
"Lower Urinary Tract Symptoms and Benign Prostatic Hyperplasia: From Research to Bedside offers full acknowledgment of the basic research of lower urinary tract symptoms (LUTS) and benign prostatic hyperplasia (BPH), also connecting the clinical and practice management of the disease. It provides a full comprehension of LUTS and BPH from several aspects, allowing for a schematic interpretation of the disease and subsequent medical management. Going beyond the guidelines in the field, this title enhances the knowledge of BPH onset, allowing for the advancement of research, beneficial clinical implication and treatment. Perfect for researchers, urologists, pathologists and endocrinologists, this must-have reference provides what is needed to understand LUTS and BPH in one easy to reference place. Provides a clear understanding of the pathological mechanisms that are present in lower urinary tract symptoms (LUTS) and benign prostatic hyperplasia (BPH)Incorporates research with the clinical aspects of LUTS and BPH, including surgical techniquesPresents an overview of LUTS and BPH in one easy to reference place."--